Internal herniation of bowel through the mesodiverticular band in adults - rare presentation - managed by laparoscopy: report of a case - Rao, T. Narayana; Parvathi, T.; Suvarchala, A. (International Journal of Research in Medical Sciences, 2017)
Meckel’s diverticulam is the most common congenital anomaly of gastrointestinal tract. Reporting a case of small bowel obstruction due to internal herniation though the mesodiverticular band, which is a very rare presentation in adults- managed by laparoscopic division of mesodiverticular band. A 35 year old patient, presented to the emergency department with intestinal obstruction. Investigations are suggestive of small bowel obstruction. Diagnostic laparoscopy was done. A meckel’s diverticulum with herniation of small bowel through the mesodiverticular band is found. The mesodiverticular band is divided. As the meckel’s diverticulam was wide mouthed directiculectomy was not done. It can be managed safely by laparoscopy and with less incidence of complications. Morbidity is minimal and rapid return of intestinal function can be achieved.